The Form of Teachers’ Reinforcement in Learning Interaction of Indonesian Language Learning of Curriculum 2013 in Public Senior High School 1 Jepara - Rinawati, Evi; Subyantoro, Subyantoro (Pascasarjana Universitas Negeri Semarang, 2019)
The purpose of this study is to find and explain the form of reinforcement educators in the interaction of learning Indonesian Curriculum 2013 at Public Junior High School 1 Jepara. This research uses class discourse design. The data were collected by the referring method, followed by techniques of Simak Bebas Libat Cakap (SBLC), recording techniques, and noting techniques. The data were analyzed by using agih method with a basic technique for the direct element (BUL). The result of the research in the form of strengthening educator in the interaction of learning in verbal and nonverbal form. The strengthening of verbal forms done by educators in the form of words and sentences. The reinforcement in the form of words done by educators in the form of words only, while the strengthening of a sentence pronounced by educators in the form of sentences to clarify the existing words. The nonverbal reinforcement by educators is strengthening in the form of mime and body movement, by approaching, with fun activities, in the form of touch, symbols, and objects. The use of verbal and nonverbal reinforcement is done by educators simultaneously.